Power-Couples and the Colocation Hypothesis Revisited - Francesco Mariotti; Karen A. Mumford; Yolanda Pena-Boquete (Institute for the Study of Labor (IZA), 2015)
We analyse the migration movements of power couples (couples where both members have at least a college degree), half power and no-power couples within Australia. We explicitly allow for potential correlation of these movements with local labour market features. Our results support the urbanisation hypothesis for ongoing couples over either the colocation or tied-mover models. Partnered college graduates like to live in major cities regardless of their gender or the qualifications of their partner.
Keywords: J3; J7; 330; gender; graduates; colocation; tied-mover; urbanisation; migration; power couples